2011
DOI: 10.1021/jp207930m
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Surface As a Catalyst Support Material for Synthesis of Single-Walled Carbon Nanotubes

Abstract: Preparation of high-quality single-walled carbon nanotubes (SWNTs) has been advanced by controlling several parameters including the catalyst and the catalyst support material. Although zeolite has been frequently used as a catalyst support material for the synthesis of SWNTs, detailed surface properties of previously employed zeolites, and thus their role as a catalyst support material, have not been 2 sufficiently clarified yet. In this study, a clean b-plane surface of silicalite-1, which is a siliceous MFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…In addition, it is seen that the low angle XRD pattern of the sample at 2θ of 0-6°shows several diffraction lines in distinct peak in the low 2θ of region. It is clearly indicated that the sample possesses a mesoporous structure [30], which is in agreement with the result of N 2 adsorption/desorption measurement.…”
Section: The Characterization Of Catalystsupporting
confidence: 89%
“…In addition, it is seen that the low angle XRD pattern of the sample at 2θ of 0-6°shows several diffraction lines in distinct peak in the low 2θ of region. It is clearly indicated that the sample possesses a mesoporous structure [30], which is in agreement with the result of N 2 adsorption/desorption measurement.…”
Section: The Characterization Of Catalystsupporting
confidence: 89%
“…Zeolites are microporous, crystalline aluminosilicates that are widely used as heterogeneous catalysts, 1-4 catalyst supports, 5,6 ion-exchangers, 7 molecular sieve membranes, 8,9 in the catalytic conversion of biomass [10][11][12] and many more advanced applications. 13 Their nal performance in all of the mentioned applications strongly depends on the accessibility of the active sites, which is largely affected by pore size and pore connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique surface structure derived from their fine primary particles, the TiO 2 nanoparticle assemblies show excellent dispersion ability of Au nanoparticles on their rough surface. [15][16][17][18][19][20][21] Metal oxides are the most commonly used supports, because they not only have high heat tolerance and mechanical strength required for very high temperatureÀhigh pressure reactions, but also provide a wide surface area for dilution effect to occur that releases reaction heat. [1][2][3][4][5][6][7][8][9][10][11] To obtain good dispersibility of NPs, the surface of metal NPs are directly modified with organic materials or the NPs are mixed with dispersion media such as fatty acids and amines with long alkyl chains.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] To obtain good dispersibility of NPs, the surface of metal NPs are directly modified with organic materials or the NPs are mixed with dispersion media such as fatty acids and amines with long alkyl chains. [15][16][17][18][19][20][21] Metal oxides are the most commonly used supports, because they not only have high heat tolerance and mechanical strength required for very high temperatureÀhigh pressure reactions, but also provide a wide surface area for dilution effect to occur that releases reaction heat. [15][16][17][18][19][20][21] Metal oxides are the most commonly used supports, because they not only have high heat tolerance and mechanical strength required for very high temperatureÀhigh pressure reactions, but also provide a wide surface area for dilution effect to occur that releases reaction heat.…”
mentioning
confidence: 99%
See 1 more Smart Citation